Angiofibroma of Soft Tissue: A Clinicopathological Study of Eight Cases With Emphasis on the Diagnostic Utility of Fluorescence In Situ Hybridization Detection for NCOA2 Rearrangement - Wang, Canming; Fan, Yuqian; Wei, Jianguo; Xu, Qiujie; Ru, Guoqing; Zhao, Ming (Frontiers in Oncology, 2022)
Background Angiofibroma of soft tissue (AFST) is a rare mesenchymal neoplasm of fibroblastic differentiation. Due to its diverse morphology and the lack of specific immunohistochemistry (IHC) markers, AFST could elicit a broad range of differential diagnosis. Several studies have disclosed in AFST recurrent gene fusions involving NCOA2, mainly AHRR–NCOA2 fusion, providing a useful approach to diagnosing this lesion. We report eight additional cases of this rare entity with emphasis on the diagnostic utility of fluorescence in situ hybridization (FISH) detection for NCOA2 rearrangement. Methods Clinicopathological data for eight AFSTs were retrieved. IHC was performed, and FISH was used to detect rearrangements involving NCOA2, DDIT3, and FUS loci. Results There were five female and three male patients, ranging in age from 29 to 69 years (median: 55 years). The patients presented mostly with a slow-growing mass in the extremities, with or without intermittent pain. All tumors were located in the lower extremities with three (27.5%) involving or adjacent to the knee joints. Tumor size ranged from 1.5 to 3.8 cm (median: 3.0 cm). Morphologically, the tumors consisted of a proliferation of uniform, bland spindle cells set in alternating myxoid and collagenous stroma with a prominent vascular network composed of countless small, branching, thin-walled blood vessels. Foci of “chicken wire”-like capillaries and medium- to large-sized blood vessels with prominent staghorn morphology were evident in two and four cases, respectively. In addition, sheets of small round cells and foci of cystic changes were observed in one each case. Degenerative nuclear atypia was identified in three cases, while mitosis and tumor necrosis were absent. By IHC, the stromal cells were variably positive for epithelial membrane antigen, desmin, and CD68. By FISH analysis, seven out of eight cases (87.5%) showed NCOA2 rearrangement, and the remaining one had increased gene copy numbers of intact NCOA2; rearrangements involving FUS (0/4) and DDIT3 (0/3) were not identified in the cases analyzed. All tumors were surgically removed, and none had recurrence at follow-up from 5 to 73 months. Conclusions FISH analysis for NCOA2 rearrangement represents a practical method for confirming the diagnosis of AFST on the basis of appropriate histomorphological backgrounds.